Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Nitrogen deposition in Mediterranean forests. - Rodà, F; Avila, a; Rodrigo, a (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Nitrogen deposition in Mediterranean forests. - Roda, F.; Avila, a; Rodrigo, A. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
The following values have no corresponding Zotero field: accession-num: 11939283
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)